Morbidity of 200 Consecutive Cases of Hand-Assisted Laparoscopic Living Donor Nephrectomies: A Single-Center Experience - Pedro W. Baron; Ramzi Ben-Youssef; Okechukwu N. Ojogho; Arputharaj Kore; D. Duane Baldwin (Journal of Transplantation)
Background. Recipients of laparoscopically procured kidneys have been reported to have delayed graft function, a slower creatinine nadir, and potential significant complications. As the technique has evolved laparoscopic donor nephrectomy technique is becoming the gold standard for living donation. Study Design. We retrospectively reviewed the data of the first 200 hand-assisted laparoscopic living donor nephrectomies performed between January 2003 and February 2009. The initial 41 donors and their recipients (Group 1) were compared to the next 159 donors and their recipients (Group 2). The estimated blood loss, serum creatinine at discharge and 6 months, and the incidence of delayed graft function and perioperative complications were analyzed. Results. The median donor serum creatinine at discharge and 6 months was 1.2 mg/dL in each group. None of the laparoscopic procedures required conversion to an open procedure, and none of the donors required perioperative blood transfusion. The median recipient serum creatinine at 6 months after transplant was 1.2 mg/dL for each group. No ischemic ureteral complications related to the laparoscopic technique were seen. Conclusions. HALDN with meticulous surgical technique allows kidney procurement with very low morbidity and no mortality. This improved safety and decreased invasiveness from laparoscopic approach may further decrease morbidity of the procedure and increase organ donation.